Implementasi Model Pembelajaran Berbasis Masalah Dalam Pendidikan Agama Islam di SMK Mahaputra Cerdas Utama - Syarifah, Sherina Zakiyah; Robiah, Siti Robiah; Khadijah, Ifah; Dyah Aryani, Wiwik (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
This study aims to explore the implementation of the Problem-Based Learning (PBL) model in Islamic Religious Education (PAI) instruction at SMK Mahaputra Cerdas Utama. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. The results indicate that the application of PBL is carried out in a structured and contextual manner by presenting real-life problems that are closely related to students’ daily lives. This model not only enhances students’ religious understanding but also contributes to the development of positive character traits such as responsibility, empathy, and discipline. Despite facing some technical challenges, PBL has proven to offer a more engaging and meaningful learning experience.